Upaya Pengenalan Huruf Menggunakan Metode SAL pada Siswa Kelas Nol Besar di TK Dahlia Mataram Semester Genap Tahun Pelajaran 2021/2022 - Tumirah, Tumirah (ANWARUL, 2022)
This research aims to determine the application of the SAL method in introducing letters to students in class zero major at Kindergarten Dahlia Mataram even semester of the 2021/2022 academic year. This research was designed using Classroom Action Research. The subjects in this study were students in class zero at TK Dahlia Mataram, totaling 15 students consisting of 6 girls and 9 boys. With research procedures: (1) planning stage, (2) action implementation stage (3) observation stage (4) reflection stage. The results of the study show that: proper use of the SAL method can introduce letters effectively to students in major zero grade at TK Dahlia Mataram even semester of the 2021/2022 academic year. Furthermore, the researcher recommends: (1) teachers who have the same difficulties can apply the SAL learning method to introduce letters to students. (2) in order to get maximum results, it is hoped that the teacher will make learning more interesting and varied